SIMULATION AND CONTROL TECHNIQUE FOR SINGLE PHASE SUB MODULE INTEGRATED PV SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The photovoltaic (PV) system that is based on sub module-integrated converters (subMICs) is capable of maximizing solar energy harvest by eradicating power losses due to intrapanel mismatch. Modeling and simulation of subMIC-based systems are important to study the effect of PV partial shading, prove new control strategies, analyze distributed system dynamics, optimize system configurations, and determine system parameters, etc. However, the simulation of such systems can be very challenging due to the large number of switching-mode power units, nonlinear nature of PV generators, and complication of the coordinating control. This project provides an effective solution to simulate and control single-phase grid-tied PV systems that are based on a practical subMICs configuration by sliding mode control. The approach includes the simplified PV cell model and averaged model for power converters, which consider all dynamic interactions among the maximum power point tracking (MPPT).